Determination of glyphosate through passive and active sampling methods in a treated field atmosphere - Morshed, Md. Mahbub; Omar, Dzolkhifli; Mohamad, Rosli; Abd. Wahid, Samsuri (Academic Journals, 2011)
The study was carried out to determine the atmospheric residues of glyphosate (N-phosphonomethylglicine) using both passive and active sampling methods in Malaysia’s tropical weather conditions. The field was treated with Roundup (Monsanto) @ 2L ha-1 using Mistblower (Solo 412). Glyphosate was sampled in 12 h day time pre and post-spray sampling events using three simple and low-cost passive air samplers (cotton gauze, cellulose filter, and PUF) and active sampling using PUF plug and quartz filter cartridges. In pre-spray sampling event, no glyphosate detection was shown in both passive and active sampling. On the other hand, post-spray passive samples data revealed that only cotton gauze among the three passive air samples showed detection in both post-spray events during which the first post-spray (2.49 ng/cm2) showed significantly higher residue measurement than that of second post-spray period (0.84 ng/cm2). In active sampling, however, no glyphosate residue was detected in any of the PUF plug samples but detected only in quartz filter samples, revealing that glyphosate is associated with particles rather than vapour in the air. The highest concentration of glyphosate (42.96µg/m3) was measured in the air at operator’s breathing zoneduring the 25 min spray application period. In the post-spray active sampling periods, glyphosate residue was significantly far below compared to the spray period concentration. Furthermore, in paired comparison between active and passive sampling methods in terms of residue uptake performance, passive sampling showed significantly better performance than the active sampling method in this study.